Biofilm highlights - Flemming, Hans-Curt; Flemming, Hans-Curt 1947-; Wingender,Jost 1955-; Szewzyk,Ulrich 1957- (Springer eBooks., 2011)
Living in biofilms is the common way of life of microorganisms, transiently immobilized in their matrix of extracellular polymeric substances (EPS), interacting in many ways and using the matrix as an external digestion and protection system. This is how they have organized their life in the environment, in the medical context and in technical systems ? and has helped make them the oldest, most successful and ubiquitous form of life.In this book, hot spots in current biofilm research are presented in critical and sometimes provocative chapters. This serves a twofold purpose: to provide an overview and to inspire further discussions. Above all, the book seeks to stimulate lateral thinking.